Facing the rain after the phase out: Performance evaluation of alternative fluorinated and non-fluorinated durable water repellents for outdoor fabrics. (February 2018) - Schellenberger, S.; Gillgard, P.; Stare, A.; Hanning, A.; Levenstam, O.; Roos, S.; Cousins, I.T.
Abstract: Fluorinated durable water repellent (DWR) agents are used to obtain water and stain repellent textiles. Due to the on-going phase-out of DWRs based on side-chain fluorinated polymers (SFP) with "long" perfluoroalkyl chains, the textile industry lacks suitable alternatives with comparable material characteristics. The constant development and optimization of SFPs for textile applications initiated more than half a century ago has resulted in a robust and very efficient DWR-technology and textiles with exceptional hydro- and oleo-phobic properties. The industry is now in the predicament that the long-chain SFPs with the best technical performance have undesirable toxicological and environmental behaviour. This study provides a comprehensive overview of the technical performance of presently available fluorinated and non-fluorinated DWRs as part of a chemical alternatives assessment (CAA). The results are based on a study with synthetic outdoor fabrics treated with alternative DWRs and tested for repellency using industrial standard and complementary methods. Using this approach, the complex structure-property relationships of DWR-polymers could be explained on a molecular level. Both short-chain SFPs and non-fluorinated DWRs showed excellent water repellency and durability in some cases while short-chain SFPs were the more robust of the alternatives to long-chain SFPs. A strong decline in oil repellency and durability with perfluoroalkyl chain length was shown for SFP DWRs. Non-fluorinated alternatives were unable to repel oil, which might limit their potential for substitution in textile application that require repellency towards non-polar liquids. Graphical abstract: Image 1 Highlights: Chemical alternatives assessment of presently available durable water repellents (DWRs). Focus on functionality as first criteria for selecting chemical alternatives. Evaluation of textile repellency with fluorinated and non-fluorinated DWRs. Durability test as basis for a comparative life-cycle assessment.